The impact of BRAC on poverty dynamics and poverty transition: results of panel data analysis - Halder, Shantana R. (BRAC, 2019)
This paper looks into the issue of economic graduation of the poor and tries to finding out the impact of BRAC's Rural Development Programme (RDP) on it. Economic graduation is defined by the upward mobility of the poor along the poverty-pyramid into non-poor status and the ability of the vulnerable non-poor to sustain their position. Here both the expenditure and perceptual methods are considered in defining poverty. For the analysis of impact a panel data set on 419 RDP members and 81 comparable non-RDP households collected twice in 1997 and 2001 were used. Results show that when poverty among non-RDP comparison households increased from 68% to 73%, it declined from 59% to 52% among RDP member households. Poverty gap also declined sharply among the latter group. Regarding poverty inequality a declining trend was observed for both of the groups. RDP made significant contribution in the upward mobility of the poor. The extreme poor RDP households did quite well in terms of upward mobility. Although the rate of overall downward mobility among RDP members was relatively less than the rate among comparison households, almost half of the RDP's initial non-poor slipped into poverty. Results of multivariate analysis show significant positive association of poverty graduation with households' initial wealth base and changes in village level infrastructure which indicate that for making significant change in the lives of the poor necessary steps should be taken for strengthening household's physical asset base and also for providing rural infrastructure.